Characterization of Botryosphaeriaceae species associated with diseased loquat (Eriobotrya japonica) in Spain. (10th June 2016) - González‐Domínguez, E.; Alves, A.; León, M.; Armengol, J.
Abstract : Loquat ( Eriobotrya japonica ) is an important subtropical fruit crop in Spain and other Mediterranean countries. In recent years, characteristic symptoms of branch canker and dieback have been observed in the main cultivated areas of loquat in Spain. The goal of this study was to identify and characterize the species of Botryosphaeriaceae associated with these symptoms. For this, 36 affected orchards were surveyed between 2010 and 2011 in six provinces of southeastern Spain. Eighty‐four isolates belonging to the family Botryosphaeriaceae were recovered from samples with symptoms. These isolates were characterized by means of phenotypical studies, DNA sequence analyses of the internal transcribed spacer (ITS) and part of the translation elongation factor 1‐ α regions, and pathogenicity tests. Ten fungal species were identified: Diplodia malorum, Diplodia olivarum, Diplodia seriata, Diplodia pseudoseriata/Diplodia alatafructa, Diplodia sp., Dothiorella sarmentorum, Neofusicoccum mediterraneum, N. parvum, Spencermartinsia plurivora and S. viticola . In addition, Diplodia eriobotryicola and Dothiorella eriobotryae are newly described. The most frequent species isolated from cankers was D. seriata and, as far as is known, this is the first report of D. malorum, and species belonging to the complex D. pseudoseriata/D. alatafructa, in Spain. All species were pathogenic to 1‐year‐old loquat plants cv. Algerie, with Diplodia sp. and S. viticola as the most virulent.